Wartime children's suffering and quests for therapy in northern Uganda - Akello-Ayebare, Grace (Netherlands Organisation, 2009)
This ethnographic study set out to examine children’s suffering and quests for therapy in the context of an ongoing civil war in northern Uganda, with an aim of generating recommendations so that their ‘right to health’ can be met. Suffering was defined as experiencing illnesses, whether due to infectious diseases or emotional distress, and quests for therapy as activities children implemented to restore normality. In effect, I investigated what wartime children identified as common illnesses which affected them and how they restored normality, whether through the use of medicines or through other coping strategies. The research findings were aimed at providing baseline information for policies and healthcare interventions consistent with children’s own needs and priorities. Central to this study was the idea that existing discourses about the healthcare needs of children of primary school age had too narrow a focus. During fieldwork I asked children what illnesses had affected them in the recent past (for example within a one month recall), how children knew they were ill, what medicines they used for their illnesses, and if illnesses were persistent what other coping mechanisms they engaged in. This study examined both boys’ and girls’ illness narratives in an attempt to generate gender dis aggregated data. Data was collected over a one year period in 2004-2005 and through regular visits to Gulu in 2006 and 2007. A survey was conducted with 165 children (N=165) aged nine to sixteen years, of whom eighty-eight (n=88) were boys and seventy-seven (n=77) were girls in addition to an extensive ethnographic follow-up of 24 children.
Keywords: Wartime children's suffering; Therapy; Northern Uganda